Penambahan Sabun-Kalsium dari Minyak Ikan Lemuru dalam Ransum: 1. Pengaruhnya terhadap Tampilan Produksi Domba - A Sudarman; K G Wiryawan; H Markhamah (Faculty of Animal Science, Bogor Agricultural University, 2008)
Since the use of fat more than 5% in ruminant diets would disturb fermentation process in the rumen, the use of fat more than 5% must be protected. The calcium soap is one form of protected fat. The objective of this research was to study the effect of calcium soap in the diets on performance of sheep. Sixteen sheep were used and divided into four groups consisted of four animals in each group. The sheep were allocated in a Randomized Block Design. The treatment diets were, R0: control diet, R1: R0 + 1.5% calcium soap, R2: R0 + 3% calcium soap and R3: R0 + 4.5% calcium soap. Data were analyzed using analysis of variance and any significant differences were further tested using contrast orthogonal. The results showed that the treatments significantly (P < 0.05) decreased daily gain, dry matter, energy and protein intake, but feed conversion ratio and water intake were not significantly affected. Key words: sheep, calcium-soap, feed intake, daily gain, water intake